Bilateral total conservative parotidectomy: a tale behind an aesthetic surgery. Issue 12 (9th December 2020) - Riju, Jeyashanth; George, Philip; Vidya, Konduru; Tirkey, Amit Jiwan
Abstract : Any facial swelling is associated with stress for the patient due to cosmesis. Especially when one has bilateral symmetrical enlarged parotids, having exhausted all available conservative management, surgery becomes the last resort; which in such cases pose specific challenges. A 29-year-old man presented with problems of bilateral symmetrical enlarged parotid lesion for 5 years, which did not have an adequate response to medical line of management. He underwent proposed surgery and was diagnosed to have chronic sclerosing parotitis (CSS). The challenges faced during surgery of this non-neoplastic inflammatory lesion, with significant fibrosis, is being described. He recovered completely without any complications related to surgery. CSS rarely affects bilateral parotid glands. Surgery, results of which are outstanding, must be considered in cases where these lesions do not respond to medical line of management. Bilateral total conservative parotidectomy with sternocleidomastoid flap reconstruction provides excellent aesthesis and improves quality of life.